1986
DOI: 10.1002/anie.198604711
|View full text |Cite
|
Sign up to set email alerts
|

P6tBu4O and P7tBu5O— the First Polycyclophosphane Oxides

Abstract: In the oxidation of polycyclophosphanes, oxygen is bound exocyclically and is not inserted into the PP bonds. The P skeleton of the educts remains intact during the oxidation. l a and its isomer, with oxygen on P3 of the five‐mem‐bered ring, and 2a and 2b are obtained from P6,tBu4, and P,tBu, respectively. Proof of the constitution of the compounds followed from the 31P{1H}‐NMR spectra, which could be taken from an NMR handbook.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

1987
1987
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 10 publications
0
2
0
3
Order By: Relevance
“…It has been found that the bicyclophosphanes PeBu( 72b) and P7But5 (93) in solution react with less than a stoichiometric amount of dry air at room temperature to form the monoxides 102/103 or 104/105, respectively. 344 When the stoichiometric amount of atmospheric oxygen is employed, the corresponding dioxides and other subsequent products are also formed. Both monoxides are produced as mixtures of two constitutional isomers (ratios 102/103 = 4.5:1; 104/105 ** 1:1);…”
Section: Polycyclophosphane Oxidesmentioning
confidence: 99%
“…It has been found that the bicyclophosphanes PeBu( 72b) and P7But5 (93) in solution react with less than a stoichiometric amount of dry air at room temperature to form the monoxides 102/103 or 104/105, respectively. 344 When the stoichiometric amount of atmospheric oxygen is employed, the corresponding dioxides and other subsequent products are also formed. Both monoxides are produced as mixtures of two constitutional isomers (ratios 102/103 = 4.5:1; 104/105 ** 1:1);…”
Section: Polycyclophosphane Oxidesmentioning
confidence: 99%
“…Baudler and co‐workers reported on ( t Bu) 4 P 6 ( 1 , Scheme ) and the related oxide ( t Bu) 4 P 6 O ( 2 ), which were derived from t BuPCl 2 and PCl 3 by reduction with Mg and subsequent oxidation by exposure to air 14. 15 As reported by the group of Jutzi, thermolysis of (Cp*P) 3 yielded the structurally related bicyclic hexaphosphane Cp* 4 P 6 ( 3 , Cp*=pentamethylcyclopentadienyl) as well as the tricyclic hexaphosphane Cp* 2 P 6 ( 4 ), which incorporates a benzvalene type P 6 scaffold ( A ) 16. 17 Weigand and co‐workers reported on the cationic compound [Ph 4 P 6 ] 2+ ( 5 ), which can formally be derived from the prismane type structure ( B ) of P 6 18.…”
Section: Methodsmentioning
confidence: 99%
“…a,x-difunktionellen Organylpolyphosphans mit einem Di(halogen)organylphosphan bzw. Nach diesem Synthesekonzept konnte auch das monooxidierte Cyclotriphosphan (PBu t ) 3 O erhalten werden. Nach diesem Synthesekonzept konnte auch das monooxidierte Cyclotriphosphan (PBu t ) 3 O erhalten werden.…”
Section: O 1±4unclassified
“…Die Korrelation von MS-und 31 P-NMR-spektroskopischen Befunden ergibt das Vorliegen von zwei konstitutionsisomeren Dioxiden 2 a und 2 b, von denen 2 a auch als Zersetzungsprodukt von Tri-tert-butylcyclotriphosphan-monoxid, (PBu t ) 3 O, gebildet wird [1]. Detaillierte Aussagen zur Struktur von 2 a ergeben sich aus dem im 31 P{ 1 H}-NMR-Spektrum beobachteten AA'XX'-System (s. oben), dessen Signallagen auf einen P 4 -Ring mit zwei exocyclisch gebundenen Sauerstoffatomen hinweisen.…”
Section: (Pbu T ) 4 O (A B)unclassified
See 1 more Smart Citation